Gridlock resolution in interbank payment systems - Morten L. Bech; Kimmo Soramäki (Bank of Finland, 2001)
The paper analyses the severity of gridlocks in interbank payment systems operating on a real time basis and evaluates by means of simulations the merits of a gridlock resolution algorithm.Data used in the simulations consist of actual payments settled in the Danish and Finnish RTGS systems.The algorithm is found to be applicable to a real time environment and effective in reducing queuing in the systems at all levels of liquidity, but in particular when intra-day liquidity is scarce
URN:NBN:fi:bof-20140807337
Keywords: 330